Prediction of the Clinical Outcomes of Sigmoid Volvulus by Abdominal X-Ray: AXIS Classification System. (15th November 2018) - Ishibashi, Rei; Niikura, Ryota; Obana, Nobuya; Fukuda, Sho; Tsuboi, Mayo; Aoki, Tomonori; Yoshida, Shuntaro; Yamada, Atsuo; Hirata, Yoshihiro; Koike, Kazuhiko
Abstract : Aim . Early diagnosis and evaluation of the severity of sigmoid volvulus are necessary for management and early intervention. We developed a new predictive classification system for sigmoid volvulus based on X-ray findings. Methods . We retrospectively analyzed 66 patients diagnosed with sigmoid volvulus using the electronic medical records at the Osaki Citizen's Hospital and the University of Tokyo Hospital from 2008–2015. We classified patients according to the coffee-bean sign mesenteric axis on X-ray (AXIS classification: group A, 0–90°; group B, 90–135°; and group C, >135°). We examined the association between AXIS classification and severe sigmoid volvulus, intestinal necrosis, need for surgery, 30-day mortality, and length of stay using the Cochran–Armitage trend test. Results . In total, 66 patients were analyzed. They had a mean age of 76.9 years, and 47 (71.0%) were male. They were classified into three groups according to the AXIS classification system (group A, 40 patients; group B, 23 patients; and group C, 3 patients). Group C had a significantly higher frequency of severe sigmoid volvulus (100%) compared to group B (30%) and group A (15%). AXIS classification was significantly associated with the severity of sigmoid volvulus (p = 0.003 ), necrosis (p = 0.004 ), and need for surgery (p = 0.001 ), but not with the 30-day mortality or the length of stay. Conclusions . We developed the AXIS classification system to predict the severity of sigmoid volvulus. This new classification system may facilitate triage and therapeutic decision-making for sigmoid volvulus patients.